The Effects of Asset Turnover and Accounts Receivable Turnover on The Profitability of Hotel X - Ni Kadek Vidya Aishwanari; I Gusti Ngurah Agung Wiryanata; A.A. Istri M. Septiviari (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Profitability is a key indicator of hotel financial performance success that is heavily influenced by the effectiveness of asset utilization and accounts receivable management. In the capital-intensive and competitive hospitality industry, the ability to optimize assets and accelerate cash flow from receivables becomes an important factor in maintaining business sustainability. This research aimed to examine the effect of asset turnover and accounts receivable turnover on profitability at Hotel X. This research employed a quantitative approach with secondary data derived from the financial statements of Hotel X, for 2020–2024. Data collection techniques include non-participant observation and a documentation study. The data analysis method is multiple linear regression with the Statistical Product and Service Solutions (SPSS) version 30 software. The results indicate that both asset and accounts receivable turnover positively and significantly affect profitability, both partially and simultaneously. This suggests that efficient management of assets and receivables can enhance the hotel’s financial performance in generating profit. The coefficient of determination shows that the independent variables explain 86.2% of the variability in profitability, while other factors outside this study influence the remaining 13.8%. The evidence confirm that efficient asset and receivables management contributes significantly to improving the profitability of Hotel X. Therefore, managerial strategies that focus on resource optimization and improvement of collection systems can strengthen the hotel's financial performance and competitiveness in the future.